Nationalism Character Education Through Local Culture and Ideological Awareness: A Literature Review of the Ideological Challenges of HTI - Utomo, Budi; Ali, Mudzakkri; Hamzah, Ghufron (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2025)
Character education that cultivates love for the homeland is a fundamental pillar in shaping a generation with strong loyalty to the nation and state. The strengthening of this character is a collective responsibility involving families, schools, communities, and the government. The absence or negligence of any of these elements can negatively affect the formation of national identity among students. This study aims to explore strategies for enhancing nationalist character through cultural education and ideological literacy, particularly in response to the ideological threat posed by organizations such as Hizb ut-Tahrir Indonesia (HTI), whose doctrines contradict the ideology of Pancasila. This research employs a qualitative method with a library research approach by reviewing relevant academic literature. The analysis process includes data collection, reduction, display, and verification to ensure the validity of findings. The results indicate that fostering love for the homeland can be strengthened through the integration of local and national culture in the curriculum. Furthermore, students must be equipped with critical awareness of transnational ideologies such as HTI that are incompatible with the foundational values of the Unitary State of the Republic of Indonesia. Therefore, Islamic education holds a strategic role in building ideological resilience among the younger generation while preserving cultural heritage as part of national identity.